1991
DOI: 10.1002/andp.19915030103
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime‐Measurements of Selectively Excited Molecular Levels

Abstract: Den Annolen, der Ph?jsik zurn 200. Geburtstag gewidmet.A h s t ract. X synchroncously pumped modc-locked cavitj -dumped dye laser, which delivers ric.arly l!'i,riricr-limited output pril.ues with 20 W peak power, 600 ps pulsewidth and 1.5 GHz spectr;iI b:intlwidth is used to populirtc selected rovibronic levels in excited electronic states of alkali moleculcs.The I;mr induccrl fluorescence is filtered through a monochromator and the lifetimes of individunl rovibronic lcvcls nro determined N ith the singlo phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…When the calculated lifetimes are divided by 4 to convert to the present Hö nl-London factors, it is seen that there is good agreement with the lifetimes measured by Bieniak et al [18]. [18]. Table 2 Hö nl-London factors for lines of low-K emission bands Transition R-line S J 0 K 0 0 ;J 00 K 00 00 Q-line S J 0 K 0 0 ;J 00 K 00 00 P-line S J 0 K 0 0 ;J 00 K 00 00 Sum over J 00 and 00 P j 00 00 S J 0 K 0 0 ;J 00 K 00 00 1 R ± fi 1 R ± J 0 0 J 0 + 1 2J 0 + 1 1 R ± fi 1 P J 0 À1 2 J 0 + 1 J 0 + 2 2(2J 0 + 1) 1 P (e) fi 1 R + J 0 + 1 0 J 0 2J 0 + 1 1 P (f) fi 1 R + 0 2 J 0 + 1 0 2J 0 + 1 1 P (e) fi 1 R À 0 2 J 0 + 1 0 2J 0 + 1 1 P (f) fi 1 R À J 0 + 1 0 J 0 2J 0 + 1 1 P (e) fi 1 P…”
Section: Application To Emission Bandssupporting
confidence: 66%
See 1 more Smart Citation
“…When the calculated lifetimes are divided by 4 to convert to the present Hö nl-London factors, it is seen that there is good agreement with the lifetimes measured by Bieniak et al [18]. [18]. Table 2 Hö nl-London factors for lines of low-K emission bands Transition R-line S J 0 K 0 0 ;J 00 K 00 00 Q-line S J 0 K 0 0 ;J 00 K 00 00 P-line S J 0 K 0 0 ;J 00 K 00 00 Sum over J 00 and 00 P j 00 00 S J 0 K 0 0 ;J 00 K 00 00 1 R ± fi 1 R ± J 0 0 J 0 + 1 2J 0 + 1 1 R ± fi 1 P J 0 À1 2 J 0 + 1 J 0 + 2 2(2J 0 + 1) 1 P (e) fi 1 R + J 0 + 1 0 J 0 2J 0 + 1 1 P (f) fi 1 R + 0 2 J 0 + 1 0 2J 0 + 1 1 P (e) fi 1 R À 0 2 J 0 + 1 0 2J 0 + 1 1 P (f) fi 1 R À J 0 + 1 0 J 0 2J 0 + 1 1 P (e) fi 1 P…”
Section: Application To Emission Bandssupporting
confidence: 66%
“…The lifetime is determined by emission to the X 1 R þ g state, the RKR potentials are from [15] and [16], and the transition-moment function from [17]. When the calculated lifetimes are divided by 4 to convert to the present Hö nl-London factors, it is seen that there is good agreement with the lifetimes measured by Bieniak et al [18]. [18].…”
Section: Application To Emission Bandsmentioning
confidence: 76%
“…The lifetimes of such perturbed levels can, in general, be shortened or prolonged [29][30][31][32] as relative to those of unperturbed levels. For example in multiexponential decays of the C(2) 1 u state of Cs 2 , the two shorter lifetimes were attributed to levels predissociating via a repulsive triplet state [29].…”
Section: Discussion Of the Lifetime Resulls And Estimation Of The Prementioning
confidence: 99%
“…From lifetimes for C(2)1Πu (red excitation) reported by Kato et al [29] one can deduce: Γp 260 s-1 ass Pp = 1930 µs-1 , for weaker and stronger predissociated levels, respectively. Bieniak et al [30] reported Γp = 45=323μis-1 for D(2) 1E,1 (υ' = 43, J' = 92=129) levels (yellow excitation) assuming the unperturbed lifetime of 18 ns.…”
Section: Discussion Of the Lifetime Resulls And Estimation Of The Prementioning
confidence: 99%
“…The vibrational and rotational molecular constants required for constructing the potential curves of X 1 Σ g + -and A 1 Σ u + -states were taken from the literature [19,20]. Radiative lifetimes of Cs 2 were measured for electronic states C [21][22][23]. Construction of Potential Curves.…”
Section: Introductionmentioning
confidence: 99%